The Impact of Organochlorine Pesticides (OCPs) on Environment Health - Saiful Jamal; Indang Dewata; Abdul Razak; Nurhasan Syah (Poltekkes Kemenkes Palu, 2023)
Pesticides are toxic chemicals used mainly in agriculture to control pests and increase production. The use of pesticides is increasing with the development of special agricultural areas in the Nagari Sungai Nanam Solok district. Organochlorine pesticides are still used to control diseases on agricultural land, while the use of organochlorine pesticides has been prohibited due to the persistent effects they produce. The research aims to look at the potential environmental impacts caused by the use of specialized organochlorines on public water resources that are vital to daily life. The study used random purposive sampling techniques to determine respondents' characteristics and the water sources used. This study's respondents comprised 85 people obtained from the village group in the Nagari Sungai Nanam district of Solok. In contrast, the water samples were obtained from Galian wells and Pamsimas facilities. The results of the study showed that the level of risk of 8 (eight) means used by society could be determined by using the IKL form: there are two means (25%) at the high-risk level, three means (37.5%) at the medium-risk level, and three means (37.5%) at the low-risk level. As a result of the water sample testing, eight sampling sites found a concentration of lindane that exceeded the threshold of 0.45 ug/L lindane in the sample L.2771 (a water well in Jorong Pasa) and 0.62 ug/LL in the L.2775 sample (well water in Jorong Taratak Pauh). This condition describes the potential for higher pollution of wells due to organochlorine-like pesticides or other types that can harm health and the environment. The high use of pesticides, if not limited, will be a danger in the future for the surrounding community, which can lead to death, so an in-depth study is needed regarding the effect of pesticide use on the health conditions of the community and its environment.